Simplified method for estimate seismic responses of continuous bridges of prestressed concrete beams - Rondón Salvatierra, Mark Michel (2021)
Continuous deck bridges of prestressed concrete beams are a type of bridge widely used in Peruvian engineering, due to the advantages that these bridges represent in the optimization of resources in the design and construction stages. The present investigation proposes simplified expressions in two directions of analysis to calculate the fundamental period of vibration of the bridge and the elastic seismic responses of lateral displacement, shear force, and a bending moment of the pier with the highest seismic demand. These expressions were obtained from the elastic seismic analysis carried out on a set of parametric models. As a seismic load, seismic design spectra were used according to isoacceleration maps specified in the bridge manual of the Peruvian Ministry of Transportation. Initially, a simplified model formulated that represents the structural elements of the bridge, then the parameters that define it is seismic behavior were identified and a large number of cases of parametric models were generated. The most representative parameters are defined as longitudinal slenderness (H/B), transverse slenderness (H/D), the aspect ratio of the plan (R/L), number of spans (nt), and peak ground acceleration (PGA). To validate the simplified model, results of interest obtained from the proposed model were compared with those obtained from refined structural models carried out in a specialized engineering program, which includes the effects of common supports and seismic stoppers. Finally, the expressions of the simplified method allow estimating seismic responses with errors of less than 10%.